2019
DOI: 10.1002/term.2992
|View full text |Cite
|
Sign up to set email alerts
|

Specific complexes derived from extracellular matrix facilitate generation of structural and drug‐responsive human salivary gland microtissues through maintenance stem cell homeostasis

Abstract: Three‐dimensional cultured salivary glands (SGs) microtissues hold great potentials for clinical research. However, most SGs microtissues still lack convincing structure and function due to poor supplementation of factors to maintain stem cell homeostasis. Extracellular matrix (ECM) plays a crucial role in regulating stem cell behavior. Thus, it is necessary to model stem cell microenvironment in vitro by supplementing culture medium with proteins derived from ECM. We prepared specific complexes from human SG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…53,54 Furthermore, salivary gland ECM is known to incorporate and release these growth factors to maintain the SGSC homeostasis microenvironment. 55 Although the key factors involved in anti-apoptotic radioprotection and tissue remodeling after irradiation must be identified, we observed that SGSC spheroid cell-implanted mice experienced lower levels of radiation-induced tissue damage through enhanced radioprotective effects, compared with SGSC monolayer cellimplanted mice during observational study for 16 weeks post-irradiation.…”
Section: Discussionmentioning
confidence: 69%
“…53,54 Furthermore, salivary gland ECM is known to incorporate and release these growth factors to maintain the SGSC homeostasis microenvironment. 55 Although the key factors involved in anti-apoptotic radioprotection and tissue remodeling after irradiation must be identified, we observed that SGSC spheroid cell-implanted mice experienced lower levels of radiation-induced tissue damage through enhanced radioprotective effects, compared with SGSC monolayer cellimplanted mice during observational study for 16 weeks post-irradiation.…”
Section: Discussionmentioning
confidence: 69%
“…For example, fibronectin induced branching and ductal elongation [ 85 ], which was enhanced with FGF7. Salivary gland ECM extract (s-Ecx) promoted a compact sphere structure and increased expression of keratins (K5, K7, K14, K19) and acinar markers such as Aqp5 and Muc-1 [ 86 ]. Chitosan has been shown to increase spheroid size and polarization [ 25 ], with the greatest effect from soluble chitosan.…”
Section: Trends In In Vitro Salivary Gland Tissue Culturementioning
confidence: 99%
“…They can recapitulate the structural and functional features of their in vivo counterparts [17][18][19] . Compared to time-consuming animal models, organoids are easy to establish and manipulate [20][21][22][23][24][25][26][27][28][29] . Importantly, they can be used to study the mechanism of human diseases that are difficult to model in animals 25,30,31 .…”
Section: Introductionmentioning
confidence: 99%